Tumor-related neurocognitive dysfunction in patients with diffuse glioma: a retrospective cohort study prior to antitumor treatment. Issue 6 (22nd April 2019) - van Kessel, Emma; Emons, Michelle A C; Wajer, Irene H; van Baarsen, Kirsten M; Broekman, Marike L; Robe, Pierre A; Snijders, Tom J; Van Zandvoort, Martine J E
Abstract: Background: Impairments in neurocognitive functioning (NCF) frequently occur in glioma patients. Both the tumor and its treatment contribute to these impairments. We aimed to quantify NCF in glioma patients before treatment and to investigate which factors influence NCF. Methods: We performed a retrospective cohort study in diffuse glioma patients according to STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) criteria. All patients had undergone neuropsychological assessment as part of routine clinical care, before awake surgery. We studied "overall NCF" and NCF in 5 neurocognitive domains separately. For "overall NCF" and per domain, we performed analyses at 2 different levels of outcome measures: (1) group level: mean cognitive functioning of the study sample, and (2) individual level: the percentage of impaired patients. We performed multivariable logistic regression analyses to investigate which factors were associated with the occurrence of cognitive impairments. Results: From our cohort of glioma patients (2010-2016), 168 patients met all the inclusion criteria. All cognitive domains were significantly affected at the group level. The percentages of neurocognitive impairments (–2SD) were highest for Executive Functioning, Psychomotor Speed, and Memory (26.5%, 23.2%, and 19.3%, respectively). Patients with high-grade glioma were affected more severely than patients with low-grade glioma. Tumor volume, isocitrate dehydrogenase status, WHO grade, and histology were associated with the occurrence of domain-specific impairments. Conclusions: Cognitive impairment occurs in the majority of treatment-naive glioma patients. The domains Executive Functioning, Speed, and Memory are involved most frequently. These impairments in NCF are explained not only by tumor location and volume, but also by other (biological) mechanisms.